The estimation of the fat free mass index in athletes - Loenneke, J. P.; Wilson, J. M.; Wray, M. E.; Barnes, J. T.; Kearney, M. L.; Pujol, T. J. (Asian Journal of Sports Medicine, 2012)
Purpose: The purpose of this investigation was to compare a practical measurement of fat free mass index (FFMI) from bioelectrical impedance analysis (BIA) to the dual energy X-ray absorptiometry (DEXA) value in collegiate athletes.